Idealism in Christian Religious Education: Concept, Implementation, and Challenges - Fallo, Abryani; Langkola, Adinda Lestari; Taek, Delni; Lopo, Diance; Tofeto, Vantri; Pellokila, Ireni Irnawati (Lembaga Penelitian dan Pendidikan Mandala, 2026)
Christian Religious Education (PAK) plays an important role in shaping students' character and moral awareness. One philosophical stream that can serve as a foundation for Christian Religious Education (PAK) is idealism. Idealism emphasizes that true reality is ideas, mind, or spirit, not material objects. This article discusses the concept of idealism in Christian Religious Education (PAK), the implementation of idealism in Christian Religious Education (PAK), and the challenges faced in implementing idealism in Christian Religious Education (PAK). Research results show that idealism can serve as a strong foundation for PAK to shape students' character and moral awareness, as well as improve the quality of Christian religious education. However, the implementation of idealism in PAK must be carried out carefully and consider existing challenges, such as limited resources, teachers' skills, inappropriate curriculum, and diverse student needs.